Silk painting - Milne, Jenni (Art of crafts, 1999)
Silk Painting provides an introduction to the colorful and exciting world of this popular art. With a few basic materials, paints in the three primary colors and black, a brush, gutta, an embroidery frame, and a piece of silk, Jenni Milne shows you how to create a wide variety of projects. Some of these give basic instructions and are ideal for the beginner; others combine techniques for the more adventurous. All of them will encourage the reader to make colorful hand-painted works of art. Silk Painting is lavishly illustrated throughout with full-color photographs, and will provide an inspiration to students, amateurs, and established artists on silk.